Calcium phosphates nanoparticles: The effect of freeze-drying on particle size reduction - Piazza, Rodolfo Debone [UNESP]; Pelizaro, Thales A.G. [UNESP]; Rodriguez-Chanfrau, Jorge E.; La Serna, Amisel Almirall; Veranes-Pantoja, Yaymarilis; Guastaldi, Antônio Carlos [UNESP] (Elsevier, 2020)
Calcium phosphate bioceramics have been widely used in medical applications, such as orthopedics and odontology, due to their similarities to the synthesized material with the calcium phosphate present in the mammals. The interest on amorphous calcium phosphates (ACP), octacalcium phosphate (OCP) and hydroxyapatite (HA) phases correspond to their ability to transform into the biological phases observed during the formation and remodeling of bone. In the present work, the freeze drying was evaluated as a simple technique to produce calcium phosphates in a nanoscale. The calcium phosphates phases were synthesized by a wet chemical method and the results showed that freeze drying do not alter the crystallinity and morphological characteristics of the samples, however the particles size were drastically reduced when compared with other drying techniques. Thus, the freeze-dry is shown to be an easy alternative to obtain nanomaterials for tissue engineering and bone regeneration.
Keywords: Bone regeneration; Calcium phosphates; Freeze-drying; Nanocrystals